Personal Branding for the Mayor of Palu via the TikTok Account @hadiantorasyid - Agung Gusnaldi; Andi Febri Herawati; Giska Mala Rahmarini (Tadulako Social Science and Humaniora Journal, 2023)
This research aims to find out how the Mayor of Palu is personally branded through the TikTok account @hadiantorasyid. The type of qualitative descriptive research with the basic case study of the research. Through the purposive sampling technique, four informants were selected, namely the Mayor of Palu, the Special Staff of the Mayor of Palu, the Chairman of the Media Center, and the Videographer of the Mayor of Palu, with data collection techniques through observation, interviews, and documentation. The results of this research show the Values and Vision, the presence of leaders who are close to their audiences, and the vision of building the City of Palu. Moral values, maintaining morals so as not to harm other parties. Be consistent, and consistently upload Content. Specialization, good exercise, and public speaking skills by the Mayor. Hobbies and Skills, Good Sports and Public Speaking by the Mayor. Authority, The supreme authority to regulate and enforce any rules. Relevant, showing the information and achievements of the Mayor clearly. Visibility, consistent major character. Persistence, the team's efforts to build Personal branding through TikTok social media. Acts of Kindness, the nature and character of the original Mayor. Content Quality Improvement, improve information quality with clear audio and clear images.